Comparison of aspirin and indobufen in healthy volunteers. (17th February 2016) - Lee, Jong-Young; Sung, Ki-Chul; Choi, Hyo-In
Abstract: The aim of this study is to quantify the extent and recovery of platelet inhibition after administration of indobufen and aspirin in healthy volunteers. Indobufen inhibits platelet aggregation by reversibly inhibiting the platelet cyclooxygenase enzyme, thereby suppressing thromboxane synthesis. Twenty healthy volunteers completed the study and received aspirin (200 mg/day for 2 weeks) followed by a 4-week washout period and then indobufen (200 mg twice a day for 2 weeks). The percent (%) inhibition of platelet aggregation (IPA) was assessed using arachidonic acid (0.5 mg/ml) and adenosine diphosphate (5 µM) at 4, 12, 24 and 48 hours after last dose of each drug. IPA assessed using arachidonic acid as the agonist was similar at 4 hours after the last dose of indobufen (81.07 ± 9.36%) and aspirin (96.99 ± 0.29%, p  = 0.10), but significantly lower at 12 hours (74.04 ± 9.55% vs. 97.94 ± 0.28%, p  = 0.02), 24 hours (33.39 ± 11.13% vs. 97.48 ± 0.32%, p  < 0.001) and 48 hours (14.12 ± 9.74% vs. 98.22 ± 0.31%, p  < 0.001) after indobufen, compared to the relative values for aspirin. IPA assessed using adenosine diphosphate as the agonist was similar in the two groups at 4, 12 and 24 hours after the last dose, but significantly lower 48 hours after the last dose of indobufen, compared to the relative value for aspirin (1.98 ± 3.57% vs. 12.61 ± 2.71%, p  = 0.002). Indobufen (200 mg twice a day) caused equivalent initial inhibition of platelet aggregation to aspirin (200 mg daily), and the anti-aggregation effect diminished faster than after aspirin.